The Effect of Knowledge, Taxpayer Awareness and Tax Sanction on the Tax Compliance - Yosy Fryli Mianti; Gideon Setyo Budiwitjaksono (Journal of Economics, Business, and Government Challenges, 2021)
This study aims to determine the effect of knowledge, awareness of taxpayers, and tax sanctions on taxpayer compliance. The population of this study is an individual taxpayer registered at the Pratama Surabaya Mulyorejo Tax Service Office and the determination of the sample using incidental sampling. This study used a sample of 100 respondents who were calculated using the Slovin formula. The sample collection method used a questionnaire which was measured using a Likert scale. The analysis technique uses Partial Least Square with WarpPLS 7.0 software. The results of this study indicate that knowledge, awareness of taxpayers, and tax sanctions have a positive effect on individual taxpayer compliance at the Pratama Surabaya Mulyorejo Tax Service Office.